Estudo comparativo, randomizado para avaliar a eficácia terapêutica da piperazina hexahidratada com extrato fluido de rhamnus purshiana no tratamento da ascaridíase - Viana, Fernando André Campos (2007)
The efficacy and the therapeutic security of a manufactured piperazina associated with the extract fluid of Rhamnus purshiana (DM Indústria Farmacêutica) used for deworming patients in Ceará, Brazil, were tested against the product composed by piperazina without any association (DM Indústria Farmacêutica). A prospective, randomized, controlled and double blind clinical trial, comparing cure rates for Ascaris lumbricoides infections. Stool samples from 990 volunteers were collected at baseline and the prevalence of intestinal parasitic infections were viewed. 130 patients with faecal sample positive for Ascaris lumbricoides were included on the clinical trial, to assess the efficacy and therapeutic security. Socio-economic and sanitation information was obtained by an oral questionnaire. More than half of the patient showed monoparasitism (60%) and prevalence of Ascaris lumbricoides was (29%) in the study population. Intestinal helminth and protozoon infections egg positive rate was 48.38% (trichuriasis 4%, ancylostomiasis 0%, amebiasis 04%, giardiasis 10%). Cure rate for piperazine associated with the extract fluid of Rhamnus purshiana was 93.33% and piperazine without any association was 96.36%, so there was no significant difference in the cure rates (P = 0.6809). The most prevalent side effects were nausea 13.84% and vomit 11.53%. There was no significant difference in the prevalence of side effects (P = 0.2348). Socio-economic and sanitation dates showed narrow relation with Ascaris lumbricoides. Piperazine associated with the extract fluid of Rhamnus purshiana was efficient and insurance in the treatment of Ascaris lumbricoides in the studied population.